Association mapping for important agronomic traits in wild and cultivated Vigna species using cross-species and cross-genera simple sequence repeat markers - Kumari, Gita; Shanmugavadivel, P. S.; Lavanya, G. Roopa; Tiwari, Pravin; Singh, Dharmpal; Gore, P. G.; Tripathi, Kuldeep; Madhavan Nair, Ramakrishnan; Gupta, Sanjeev; Pratap, Aditya (Frontiers in Genetics, 2022)
The genus Vigna is agronomically important taxa with many of its species inhabiting a wide range of environments and offering numerous useful genes for the improvement of the cultivated types. The present study aimed at detecting the genomic regions associated with yield attributing traits by genome-wide association mapping. A diverse panel of 98 wild and cultivated Vigna accessions (acc.) belonging to 13 different species was evaluated for yield and related traits during kharif season of 2017 and 2018. The panel was also genotyped using 92 cross genera and cross species simple sequence repeat (SSR) markers to study population genetic structure and useful market-trait associations. The PCA and trait correlation established relationships amongst the traits during both the seasons while 100-seed weight (HSW) had positive correlation with pod length (PL), and days to first flowering (DFF) with days to maturity (DM). The population genetic structure analysis grouped different acc. in three genetically distinct sub-populations with SP-1 comprising 34 acc., SP-2 (24 acc.), SP-3 (33 acc.) and one admixture group (7 acc.). Mixed Linear Model (MLM) analysis revealed association of 13 markers namely VR018, VR039, VR022, CEDG033, GMES0337, MBSSR008, CEDG220, VM27, CP1225, CP08695, CEDG100, CEDG008, and CEDG096A with 9 traits. 7Seven of the above markers viz., VR018 for plant height (PH) and terminal leaflet length (TLL), VR022 for HSW and PL, CEDG033 for DFF and DM, MBSSR008 for DFF and DM, CP1225 for chlorophyll content at 30 days (CC30), DFF and DM, CEDG100 for PH and terminal leaflet length (TLL), and CEDG096A for CC30 and chlorophyll content at 45 days were associated with multiple traits. The marker CEDG100 associated with HSW, PH and TLL is co-localized in gene encoding histone-lysine N-methyltransferase ATX5. Similarly, VR22 associated with PL and HSW is co-located in gene encoding SHOOT GRAVITROPISM 5 in mungbean. These associations may be highly useful for marker-assisted genetic improvement of mungbean and other related Vigna species.